Revascularisation and mortality rates following acute coronary syndromes in people with severe mental illness: comparative meta-analysis - Mitchell, A.; Lawrence, David (Royal College of Psychiatrists, 2011)
Background: High levels of comorbid physical illness and excess mortality rates have been previously documented in people with severe mental illness, but outcomes following myocardial infarction and other acute coronary syndromes are less clear. Aims: To examine inequalities in the provision of invasive coronary procedures (revascularisation, angiography, angioplasty and bypass grafting) and subsequent mortality in people with mental illness and in those with schizophrenia, compared with those without mental ill health. Method: Systematic search and random effects meta-analysis were used according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies of mental health and cardiovascular procedures following cardiac events were eligible but we required a minimum of three independent studies to warrant pooling by procedure type. We searched Medline/PubMed and EMBASE abstract databases and ScienceDirect, Ingenta Select, SpringerLink and Online Wiley Library full text databases. Results: We identified 22 analyses of possible inequalities in coronary procedures in those with defined mental disorder, of which 10 also reported results in schizophrenia or related psychosis. All studies following acute coronary syndrome originated in the USA. The total sample size was 825 754 individuals.Those with mental disorders received 0.86 (relative risk, RR: 95% CI 0.80–0.92, P50.0001) of comparable procedures with significantly lower receipt of coronary artery bypass graft (CABG; RR = 0.85, 95% CI 0.72–1.00), cardiac catheterisation (RR = 0.85, 95% CI 0.76–0.95) and percutaneous transluminal coronary angioplasty or percutaneous coronary intervention (PTCA/PCI; RR = 0.87, 95% CI 0.72–1.05). People with a diagnosis of schizophrenia received only 0.53 (95% CI 0.44–0.64, P50.0001) of the usual procedure rate with significantly lower receipt of CABG (RR = 0.69, 95% CI 0.55–0.85) and PTCA/PCI (RR = 0.50, 95% CI 0.34–0.75). We identified 6 related studies examining mortality following cardiac events: for those with mental illness there was a 1.11 relative risk of mortality up to 1 year (95% CI 1.00–1.24, P = 0.05) but there was insufficient evidence to examine mortality rates in schizophrenia alone. Conclusions: Following cardiac events, individuals with mental illness experience a 14% lower rate of invasive coronary interventions (47% in the case of schizophrenia) and they have an 11% increased mortality rate. Further work is required to explore whether these factors are causally linked and whether improvements in medical care might improve survival in those with mental ill health.